Historicizing online politics : telegraphy, the Internet, and political participation in China - Zhou, Yongming, 1963- (Stanford : Stanford University Press, 2006)
It is widely recognized that internet technology has had a profound effect on political participation in China, but this new use of technology is not unprecedented in Chinese history. This is a pioneering work that systematically describes and analyzes the manner in which the Chinese used telegraphy during the late Qing, and the internet in the contemporary period, to participate in politics. Drawing upon insights from the fields of anthropology, history, political science, and media studies, this book historicizes the internet in China and may change the direction of the emergent field of Chinese internet studies. In contrast to previous works, this book is unprecedented in its perspective, in the depth of information and understanding, in the conclusions it reaches, and in its methodology. Written in a clear and engaging style, this book is accessible to a broad audience.
Introduction -- Telegraphy, culture, and policymaking -- Telegraphy, newspapers, and public opinion -- Telegraphy, political participation, and state control -- Public telegrams and nationalist mobilizations -- Telegraph power : textual and historical contexts -- China and the Internet : proactive development and control -- Negotiating power online : the party state, intellectuals, and the Internet -- Living on the cyber border : Minjian online political writers in China -- Informed nationalism : military web sites in Chinese cyberspace.
Includes bibliographical references (pages 275-281) and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
eBooks on EBSCOhost
Keywords: Political participation -- Technological innovations -- China; Telegraph -- China -- History -- 19th century; Internet -- Political aspects -- China; Internet in public administration -- China; Participation politique -- Innovations -- Chine; Télégraphe -- Chine -- Histoire -- 19e siècle.; Internet -- Aspect politique -- Chine; Administration publique en ligne -- Chine; POLITICAL SCIENCE -- Political Process -- General; Political participation -- Technological innovations; Internet in public administration; Internet -- Political aspects; Telegraph; China; Politisches Engagement; Telegrafie; Internet; China; Political participation -- Technological innovations -- China; Telegraph -- China -- History -- 19th century; Internet -- Political aspects -- China; Internet in public administration -- China; 1800-1899; History